Management of the Clinical and Academic Mission in an Urban Otolaryngology Department During the COVID-19 Global Crisis. (July 2020) - Batra, Pete S.; LoSavio, Phillip S.; Michaelides, Elias; Revenaugh, Peter C.; Tajudeen, Bobby A.; Al-khudari, Samer; Husain, Inna; Papagiannopoulos, Peter; Smith, Ryan; Stenson, Kerstin M.; Wiet, R. Mark
Objective: The objective of this study was to assess the strategic changes implemented in the departmental mission to continue safe delivery of otolaryngology care and to support the broader institutional mission during the COVID-19 pandemic response. Study Design: Retrospective assessment was performed to the response and management strategy developed to transform the clinical and academic enterprise. Setting: Large urban tertiary care referral center. Results: The departmental structure was reorganized along new clinical teams to effectively meet the system directives for provision of otolaryngology care and support for inpatient cases of COVID-19. A surge deployment schedule was developed to assist frontline colleagues with clinical support as needed. Outpatient otolaryngology was consolidated across the system with conversion of the majority of visits to telehealth. Operative procedures were prioritized to ensure throughput for emergent and time-critical urgent procedures. A tracheostomy protocol was developed to guide management of emergent and elective airways. Educational and research efforts were redirected to focus on otolaryngology care in the clinical context of the COVID-19 crisis. Conclusion: Emergence of the COVID-19 global health crisis has challenged delivery of otolaryngology care in an unparalleled manner. The concerns for preserving health of the workforce while ethically addressing patient career needs in a timely manner has created significant dilemmas. A proactive, thoughtful approach that reorganizes the overall departmental effort through provider and staff engagement can facilitate the ability to meet the needs of otolaryngology patients and to support the greater institutional mission to combat the pandemic.